FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI MAHASISWA PENDIDIKAN EKONOMI TENTANG ETIKA AKUNTAN PROFESIONAL - Ria Wani Br Purba; Gusnardi Gusnardi; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Professional ethics is very important for professionals in accounting.However, there are many accountants who also provide advice to clients to be audited.Professional ethics is very important for accountants, so the focus of ethics learning isvery important for accounting education students, because students are the startingpoint for the development of the accounting profession. The purpose of this study was todetermine the significant influence of intellectual intelligence, locus of control, andreligiosity on students' perceptions about the ethical of professional accountants. Thesampling method uses a sensus sampling where the entire population is sampled, thenumber of samples in this study amounted to 43 people who are students of economiceducation who are concentrated in accounting at the 2016 University of Riau. The dataanalysis technique used is multiple linear regression. Based on the research obtainedfrom the results of this study, significant intelligence is not significant on students'perceptions of the accountant's ethical, locus of control significantly evaluates students'perceptions of the accountant's ethical with negative relationship direction andsignificant religiosity towards students' perceptions of accountant accountability issues.This article can provide contributions and comparisons of accounting related topeople's perceptions, and can increase student awareness to be able to prepare theirthoughts and perceptions before starting the world of work.Key Words: Intellectual Intelligence, Locus Of Control, Religiosity, Students' Perceptions